Code-Switching as a Mediational Tool in EFL Classrooms: Students’ Attitudes, Perceptions, and Learning Experiences - Laimena, Marce; Fenanlampir, David L.; Binnendyk, Sophia (Jurnal Tahuri, 2024)
This study investigates how local linguistic features and perceptions of This study examines code-switching as a mediational tool in English as a Foreign Language (EFL) classrooms by focusing on students’ attitudes, perceptions, and learning experiences. Although teacher code-switching between English and Bahasa Indonesia is prevalent in Indonesian EFL settings, previous research has largely emphasized teachers’ linguistic and pedagogical intentions, overlooking students’ perspectives as active participants in mediated learning. Using a mixed-method design, the study involved 100 students from grades X–XII at SMA PGRI 2 Kairatu, selected through simple random sampling. Quantitative data were gathered through questionnaires measuring cognitive, affective, and behavioral dimensions of attitudes and perceptions, analyzed using descriptive statistics, correlation tests, and regression via SPSS. Qualitative data were collected through semi-structured interviews with 10–15 purposively selected students and analyzed thematically with data triangulation. Findings indicate that students generally hold positive attitudes toward code-switching, viewing it as a facilitative tool that bridges comprehension gaps, reduces anxiety, and promotes engagement, while also expressing concern about potential overreliance on the mother tongue. Drawing on Vygotsky’s sociocultural theory, the study reframes code-switching as a cognitive and pedagogical scaffold. Conducted in eastern Indonesia, it contributes a rarely represented context to global EFL discourse, advances theoretical discussions on bilingual classroom interaction, and offers pedagogical and policy implications for functionally informed, context-sensitive code-switching practices.